Efficacy and safety of awake prone positioning in the treatment of non-intubated spontaneously breathing patients with COVID-19-related acute respiratory failure: A systematic review and meta-analysis - Jingjing Wang; Daonan Chen; Puyu Deng; Chenchen Zhang; Xue Zhan; Hui Lv; Hui Xie; Dechang Chen; Ruilan Wang (Journal of Intensive Medicine, 2023)
Background: Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, prone positioning has been widely applied for non-intubated, spontaneously breathing patients. However, the efficacy and safety of prone positioning in non-intubated patients with COVID-19-related acute hypoxemic respiratory failure remain unclear. We aimed to systematically analyze the outcomes associated with awake prone positioning (APP). Methods: We conducted a systematic literature search of PubMed/MEDLINE, Cochrane Library, Embase, and Web of Science from January 1, 2020, to June 3, 2022. This study included adult patients with acute respiratory failure caused by COVID-19. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed, and the study quality was assessed using the Cochrane risk-of-bias tool. The primary outcome was the reported cumulative intubation risk across randomized controlled trials (RCTs), and the effect estimates were calculated as risk ratios (RRs; 95% confidence interval [CI]). Results: A total of 495 studies were identified, of which 10 fulfilled the selection criteria, and 2294 patients were included. In comparison to supine positioning, APP significantly reduced the need for intubation in the overall population (RR=0.84, 95% CI: 0.74–0.95). The two groups showed no significant differences in the incidence of adverse events (RR=1.16, 95% CI: 0.48–2.76). The meta-analysis revealed no difference in mortality between the groups (RR=0.93, 95% CI: 0.77–1.11). Conclusions: APP was safe and reduced the need for intubation in patients with respiratory failure associated with COVID-19. However, it did not significantly reduce mortality in comparison to usual care without prone positioning.